Economic Growth, Financial Development and Carbon Emissions. Does Institutional Quality Matter? - Kinuthia, Peter; Kemboi, Issac's; Onyango, James; Adaramola, Muyiwa Samuel (The Journal of Financial, Accounting, and Economics, 2025)
This study investigates the moderating role of institutional quality on the relationship between economic growth, financial development and carbon missions in Sub-Saharan Africa using a fixed effects panel regression model. The analysis reveals that economic growth and financial development have a positively and significantly relationship with carbon emissions, suggesting that these factors contribute to environmental degradation when sustainability measures are lacking. Conversely, institutional quality exhibit negative and significant effects on emissions, highlighting its potential in mitigating environmental harm. Importantly, interaction terms show that institutional quality moderates the positive effects of economic growth and financial development on carbon emissions, implying that strong institutions can reduce the environmental costs of development. These findings underscore the critical role of institutional quality in shaping the environmental outcomes of economic and financial progress. Policy recommendations include strengthening institutional frameworks, promoting green finance, and aligning economic growth with sustainable development goals to achieve low-carbon growth in the region.